METHODOLOGY AND SKILLS PROBLEMS - NEMATOVNA, AKHMEDOVA SHOIRA; SAIDBURKHONOVNA, KADYROVA NASIMA; BEKMURODOVNA, KURBANOVA OLTINOY (The journal of contemporary issues in business and government, 2021)
The study of the skills, style and originality of the critic is one of the most important and urgent problems of literary criticism. While the issue of the writer's style has been studied in Uzbek literature, the issue of the style and skill of the critics has been neglected. Therefore, in our study, we aimed to study the unique style and skills of critics. In this regard, in this article we present our views on the style and skill of the great literary critic I. Hakkulov and critic I. Gafurov. Their research and skills in the study of Uzbek literature, as well as aspects of their style are studied.